2012
DOI: 10.1111/j.1464-5491.2011.03412.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an evidence base for frequency of monitoring glycated haemoglobin levels in patients with Type 2 diabetes: projections of effectiveness from a regression model

Abstract: In patients with initial HbA1c close to treatment goal, retesting at 6 months would yield more true-positive than false-positive tests. For patients with lower initial HbA1c, retesting at 6 months would yield more false than true-positive tests. In all patients, retesting at 12 months yields more true than false-positive tests. In very few patients would retesting at 3 months be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…30,32,206,207 These analyses are consistent with such previous research, showing that frequent measurement of lipid levels is more likely to identify change owing to biological variability and inherent measurement error than true changes in an individual's health status. As clinical decisions on treatment are based upon these measurements, this may be detrimental to a patient's health.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…30,32,206,207 These analyses are consistent with such previous research, showing that frequent measurement of lipid levels is more likely to identify change owing to biological variability and inherent measurement error than true changes in an individual's health status. As clinical decisions on treatment are based upon these measurements, this may be detrimental to a patient's health.…”
Section: Discussionsupporting
confidence: 80%
“…The high variability in each lipid measurement resulted in recommendations for unnecessary initiation or up-titration (false-positive ) and undertreatment (false-negative) in all patient groups and under all scenarios considered. Consistent with previous research on long-term chronic conditions such as hypertension, renal function and hypercholesterolaemia, 30,204,206,207 we found that more frequent monitoring resulted in a higher proportion of false-positive tests, which, in these analyses, corresponds to a higher proportion of patients incorrectly recommended for a statin prescription or an up-titration. This is attributable to the low true rate of change over time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The model has been subsequently applied to blood pressure monitoring 36 and it has been developed further for monitoring HbA 1c 37 and microalbuminuria in diabetes. 38 In general the model needs to allow for variation between people, for average rate of change and variation in rate of change between people, and for the error rate in any individual test; we have recently published full details of the methodology.…”
Section: Introductionmentioning
confidence: 99%
“…136,137 Using these methods, annual monitoring of cholesterol and blood pressure has been shown to lead to more false-positive tests than true-positive tests: that is, a positive test for high cholesterol (or high blood pressure) is more likely to arise from measurement error than from 'true change'. 134 For many clinical monitoring tests, the variability within each measurement is greater than the likely change over 1 year, and regular cycles of testing create repeated opportunities for the occurrence of false-positive tests.…”
mentioning
confidence: 99%